Primary health care in Tanzania through a health system lens : a history of the struggle for universal health coverage - Kapologwe, Ntuli A., (editor); Kengia, James Tumaini, (editor); Praag, Eric van, (editor); Killewo, J. Z. J., (editor); Kalolo, Albino (CAB International, 2023)
"Robust health care is paramount for the health and prosperity of people and countries as a whole. Providing a chronicle of universal health coverage in Tanzania, this book is written to allow the application of lessons learned across to other country contexts, and covers policy and governance, practical health system delivery and resilience"--